Léxico especializado y léxico dialectal andaluz: voces de la construcción en documentos notariales del AHPC = Technical vocabulary and Andalusian dialect lexicon: voices of construction in AHPC notarial documents (Estudios Humanísticos. Filología, 2020)
A partir de la documentación notarial del AHPC, analizamos algunas voces del léxico de la construcción con objeto de comprobar la incidencia de aparición de este vocabulario sectorial y de examinar su grado de diferenciación diatópica. Se trata de valorar la relevancia de estas fuentes para el estudio histórico del vocabulario de especialidad en general y del dialectal andaluz en particular. Based on the notarial documentation from the AHPC, we analyze some voices from the construction lexicon in order to verify the incidence of the appearance of this sectoral vocabulary and to examine its degree of diatopic differentiation. The aim is to assess the relevance of these sources for the historical study of specialty vocabulary in general and of the Andalusian dialect in particular